ADDRESSING THE STUNTING PREVALENCE AMONG THE BAJAU COMMUNITY IN THE REGENCY OF BUTON, SOUTHEAST SULAWESI:: AN INCLUSIVE APPROACH - Sudarmono Sudarmono; Agung Muhammad Sirajd (ipdn, 2025)
Stunting is one of the challenges to realizing the Golden Indonesia 2045. Thus, stunting is currently a national priority issue due to the stunting prevalence movement at the national and regional levels. There is a quite contrasting gap in stunting rates seen in the islands of Southeast Sulawesi Province, especially Buton Regency. More than that, there is a Bajau Tribe community that lives side by side with mainland communities where the stunting rate is very high, it is influenced by economic conditions, education, and underdeveloped health facilities. With the formation of the Stunting Acceleration Team by the Buton Regency Regional Government, a collaboration process occurs between stakeholders. Thus, this study aims to analyze the relationships that occur during the collaboration process in preventing and handling stunting in the Bajau tribe community in Buton Regency. Through a qualitative-descriptive approach where data was collected through observation, interviews, documentation, audio-visual, and digital materials, this study found that the interactions that occur between stakeholders occur well, especially the interaction between the government and the community. However, there are several obstacles influenced by the social conditions of the Bajau community that hinder the exchange of information and the active participation of the community in the stunting reduction program.